Corporate Taxes and Financial Performance of Small and Medium Enterprises in Nigeria - Adewale Olusesan Taiwo; Godwin Emmanuel Oyedokun (Journal of Accounting and Taxation, 2022)
The study examined the effect of Corporate Taxes and Financial performances of Small and Medium Enterprises in Nigeria. The objective is to investigate the extent to which various Corporate Income taxes and Education taxes have affected the financial performances of Small and Medium Enterprises in Nigeria. The study adopted the Longitudinal research design using Secondary data with ordinary least square regression technique of analysis and time series data. The sample population of all SMEs in Nigeria of about 41.5million based on judgmental Sampling to obtain numerical values of model coefficient with the use of E-views version 9. The findings revealed that the company’s income tax has a positive and insignificant effect on the financial performance of small and medium enterprises in Nigeria while education tax has a negative and significant relationship with the financial performance of small and medium enterprises in Nigeria. The study concludes that the financial performance of small and medium enterprises in Nigeria is driven by Companies’ income tax, Education Tax, and Personal Income Tax. It, therefore, recommended that business entities should have knowledge on how to calculate the amount of tax payable based on the available information role of taxation in economic development should be used for social sustainability to achieve per capita income for an improved standard of living by citizens